The impact of sports participation on school inclusion degree of the left-behind and migrant children-An empirical study based on China national survey data - LIU Shu-hong; CAO Ji-hong , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The percentage of left-behind and migrant children's (MC) school enrollment is crucial to their healthy development and China's urbanization and social change processes. This study examines the effect of sports involvement on the school inclusion rate of China's left-behind and MC students. This study selects data from the China Education Panel Survey for 2013-2014. (CEPS). The ANOVA and LSD multiple comparison analyses were used to statistically examine the school inclusion gap between children who were left behind, migrant, and urban. Among left-behind and MC, the association between sports participation, interpersonal ability, and school inclusion degree was empirically tested and analyzed using a bias-corrected nonparametric percentile technique via the SPSS plug-in process. Secondly, the statistics indicate that the percentage of left-behind and MC children who attend school is much lower than that of urban children. Secondly, the results suggest that sports engagement considerably impacts school inclusion in terms of those who have fallen behind and those with disabilities. In addition, the investigation of the mediating mechanism reveals that social and interpersonal skill partially mediates the relationship. In terms of individual and family variables, the results indicate that gender, age, family economic situations, and the father's educational level substantially impact the degree of school inclusion.